Equilibrium Valuation of Foreign Exchange Claims - BAKSHI, GURDIP S.; CHEN, ZHIWU (Journal of Finance, 1997)
ABSTRACT This article studies the equilibrium valuation of foreign exchange contingent claims. Within a continuous‐time Lucas (1982) two‐country model, exchange rates, interest rates and, in particular, factor risk prices are all endogenously and jointly determined. This guarantees the internal consistency of these price processes with a general equilibrium. In the same model, closed‐form valuation formulas are presented for currency options and currency futures options. Common to these formulas is that stochastic volatility and stochastic interest rates are admitted. Hedge ratios and other comparative statics are also provided analytically. It is shown that most existing currency option models are included as special cases.